Continuties in Market Sensing - Prince, Melvin; Priporas, Constantinos-Vasilios (Market Sensing Today, 2015)
The concept and framework of market sensing was introduced by George Day more than 20 years ago into the strategic marketing literature and especially the philosophy of the market-driven organization. Market sensing can be considered an expression of a company's capabilities to scan the external environment. It does this by using real time data and intelligence to understand business or uncertain changes, to meet the current and future needs of the market, increase customer value, and outperform competitors. Market sensing enables managers to resist complacency, as well as to exploit opportunities and to design appropriate competitive strategies in order to remain successful in today's uncertain, rapidly changing, and hypercompetitive market. The present volume, Market Sensing Today, is essential reading in the marketing discipline, given the rapidly escalating innovative developments in market sensing techniques. This book of essays by acknowledged experts in the field fills an important knowledge gap and provides a realistic basis for strategy. It is replete with real-life examples of market sensing that illustrate actionable ideas for immediate impact that will improve organizational learning and accelerate growth. This book of contemporary tested and comprehensive concepts and methods grounded in diverse and rich experience is intended to stimulate creativity and insightful approaches for educators offering courses in strategy as well as for practitioners involved in crucial strategic decision making.
Keywords: Business & Economics / Marketing / General; Marketing research; dept.mkt; faculty_collection